Recent progress and development of TiO2 thin film photocatalysts for pollutant removal - Abd Aziz, Radhiyah; Iis, Sopyan (Bentham Science, 2009)
This review paper is to give an overview of the recent progress on the development of TiO2 thin film photocatalysts for pollutant removal. Photocatalysis process involves the photoinduced oxidation and reduction reactions in the photocatalyst that has the ability in degrading most organic compounds into carbon dioxide, water and any harmless substances. Upon the exposure of ultraviolet light of wavelength λ < 390nm, the photocatalyst plays its role in degrading any kind of pollutants either in liquid or gaseous phase. One of the most outstanding photocatalysts that has received particular attention in application is titanium dioxide due to its high chemical stability and photocatalytic activity. The development of the photocatalyst in the form of a thin film is due to the impractical use of conventional powder photocatalyst in certain environmental applications. Recent patents of the thin film photocatalyst as well as some environmental applications have also been reviewed. Also included are techniques for modifying thin film characteristics, film deposition methods and variation in types of substrates used for improved photocatalytic properties of the TiO2 thin film.